Respuesta :

Answer:

B, C and D.

Step-by-step explanation:

3m=36-6m

9m=36

m=4

-1/3m+2=-1

-1/3m=-3

m=9

So not it

B, c and d is the same as they all equal to 4.

Answer:

The answer to your question is b, c and d

Step-by-step explanation:

Equation given

                        3m = 36 - 6m

                        3m + 6m = 36

                        9m = 36

                          m = 36/9

                         m = 4

Equation a

                        -1/3 m + 2 = -1

                        -1/3 m = -1 - 2

                        -1/3 m = -3

                               m = -3 x -3

                              m = 9

Equation b

                       -2(-4m - 6.4) = 44.8

                            -4m - 6.4 = 44.8/-2

                            -4m = -22.4 + 6.4

                            -4m = -16

                                m = -16/-4

                               m = 4

Equation c

                       8m - 5 - 2m + 1 = 20

                       6m = 20 + 4

                        6m = 24

                          m = 24/6

                         m = 4

Equation d

                       7m + 6 = 9m - 2

                       7m - 9m = -2 - 6

                             - 2m = -8

                                 m = -8/-2

                                 m = 4

ACCESS MORE